Diversity in a multicultural and polyethnic world: challenges and responses - Du Toit, Cornel W. (Verbum et ecclesia, 2004)
Today’s world is characterised by multiculturalism. The diversity of cultures and conflicting ethnic groups sharing the same territory pose a threat to both local and world peace. We have come to the end of the ‘nation’ and the end of the ‘state’, two homogenous entities which are increasingly being emasculated by an instrumental reason in the form of techno-science and economic globalisation. Ethnic diversity is simultaneously a source of wealth and a threat to African societies. African unity in the form of an ubuntu-ethic offers a model for dealing with polyethnicity. Ethnocentrism is biologically rooted and operates through prejudice. As a coping mechanism for dealing with diversity, prejudice has its value and its limitations. It must be contained where it leads to xenophobia, ethnophobia and war. Polyethnic coexistence is a prerequisite if Africa is to attain its developmental ideals as expressed in the NEPAD programme. In this paper, I look at the way in which ethno-philosophy and ethno-theology can help this process.